Real-world evidence comparing early and late pancreatic stent placement to prevent post-ERCP pancreatitis - Wang, Shaofei; Bai, Bingqing; Huang, Qiming; Fang, Yuanyuan; Zhang, Chenyu; Chen, Xinwen; Hong, Jianglong; Jie, Lei; Ding, Hao; Hu, Cui; Li, Hongye; Li, Yang; Liu, Xiaochang; Hong, Rutao; Bao, Junjun; Mei, qiao (Endoscopy International Open, 2024)
Background and study aims Pancreatic stenting effectively lowers the occurrence of post-ERCP pancreatitis (PEP) and reduces its severity. However, limited research has been conducted to determine the optimal timing for pancreatic stent placement. Our objective was to evaluate whether early pancreatic stent placement (EPSP) is more effective than late pancreatic stent placement (LPSP) in preventing PEP among patients with naive papilla.Patients and methods We conducted a retrospective cohort study that analyzed 590 patients with difficult biliary cannulation using the pancreatic guidewire technique, who were divided into EPSP and LPSP groups. In the EPSP group, a pancreatic stent was placed immediately before/after endoscopic retrograde cholangiography (ERC) or endoscopic sphincterotomy (EST). Conversely, in the LPSP group, a pancreatic stent was placed after partial/all completion of major endoscopic procedures.Results From November 2017 to May 2023, 385 patients were in the EPSP group and 205 in the LPSP group. EPSP was associated with a decreased PEP occurrence compared with LPSP (2.9% vs. 7.3%; P = 0.012). Similarly, hyperamylasemia was lower in the EPSP group (19.7% vs. 27.8%; P = 0.026). Furthermore, sensitivity analysis using multivariable analysis and propensity score–matched (PSM) analysis also validated these findings.Conclusions Early pancreatic stent placement reduced the incidence of PEP and hyperamylasemia compared with late pancreatic stent placement. Our findings favor pancreatic stenting immediately before/after ERC or EST.
Keywords: Pancreatobiliary (ERCP/PTCD); ERC topics; Statistics